Recurrent mucinous carcinoma with sarcomatoid and sarcomatous mural nodules: a case report and literature review - Li, Simin; Zhu, Jingyu; Jiang, Na; Guo, Yanping; Hou, Meng; Liu, Xi; Yang, Jin; Yang, Xiaofeng (Frontiers in Oncology, 2024)
Ovarian mucinous tumors with sarcomatous mural nodules are rare. Sarcomatous nodules have a bad prognosis. Its diagnosis and treatment are controversial.It is still controversial whether malignant mural nodules represent a dedifferentiated form of mucinous tumors or collisional tumors. This is a case report of a 32-year-old female diagnosed with ovarian mucinous tumor recurred as a mucinous carcinoma combined with sarcomatoid and undifferentiated sarcoma mural nodules after surgery and chemotherapy. The primary lesion did not have a sarcomatous component after comprehensive sampling and repeated review, while the recurrent lesion had a predominantly sarcomatous component. The patient received a second operation and postoperative chemotherapy plus Anlotinib with no progression at 16 months of follow-up. Primary mucinous carcinoma and sarcomatous mural nodules revealed the same K-RAS mutation(c.35G>T, pG12V), TP53 mutation (c.817C>T, p.R273C), MLL2 mutation(c.13450C>T, p.R4484) and NF1 mutation(c.7876A>G, p.S2626G). We present a comprehensive analysis on morphologic characteristics, molecular detection results, clinical management, and prognosis of ovarian mucinous tumors with mural nodules of sarcomatoid and undifferentiated sarcoma. Mutation sharing between primary mucinous carcinoma and recurrent sarcomatous nodules supports monoclonal origin of primary and recurrent tumors, suggesting a tendency for sarcomatous differentiation during the progression of epithelial tumors. Malignant mural nodules represent dedifferentiation in mucinous ovarian tumors rather than collision of two different tumor types. Therefore, it is imperative to conduct comprehensive sampling, rigorous clinical examination, and postoperative follow-up in order to thoroughly evaluate all mural nodules of ovarian mucinous tumors due to their potential for malignancy and sarcomatous differentiation.